Stretch reflexes of triceps surae in patients with upper motor neuron syndromes. - Berardelli, A (1983)
Electromyographic responses of triceps surae to dorsiflexion stretch were studied in 47 patients with a variety of lesions producing an upper motor neuron syndrome. The short latency spinal reflexes, both when the patient was at rest and when he was exerting a voluntary plantarflexion, were frequently enhanced in magnitude and the rate of increase with acceleration was also enhanced. Long-latency reflexes were uncommon at rest. With background force long-latency reflexes were present unless the short latency reflex was very large. Long latency reflexes often were normal, but in some patients they were either excessively larger or even of abnormal shape with prolonged continuous activity. The clinical assessment of the ankle jerk correlated with the magnitude of the short latency reflex. The clinical assessment of tone correlated with the magnitude of the short latency reflex, the magnitude of the long latency reflex and the duration of the long latency reflex. There appear to be multiple physiological mechanisms underlying the clinical phenomenon of spasticity.